2003
DOI: 10.1177/001698620304700404
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Effective Teachers of Gifted Students: Teacher Background and Personality Styles of Students

Abstract: This study was designed to explore characteristics of exceptional teachers of gifted students. Participants included 63 teachers and 1,247 highly able students. Teachers responded to 2 measures: a background questionnaire and the Myers Briggs Type Inventory (MBTI), a self-report personality inventory. Students also completed the MBTI. In response to the background questionnaire, the majority of teachers reported holding advanced degrees in a content area; most were not certified to teach and reported completin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
78
0
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(88 citation statements)
references
References 17 publications
5
78
0
5
Order By: Relevance
“…Gifted students viewed academic support as the foundation for positive relationships, as they felt that these behaviours allowed teachers to fulfil their primary role of educational facilitators. These findings were consistent with findings from other studies involving gifted students (Gentry et al, 2007;Mills, 2003;Suk-Un Jin & Moon, 2006).…”
Section: Students With Ebdsupporting
confidence: 93%
“…Gifted students viewed academic support as the foundation for positive relationships, as they felt that these behaviours allowed teachers to fulfil their primary role of educational facilitators. These findings were consistent with findings from other studies involving gifted students (Gentry et al, 2007;Mills, 2003;Suk-Un Jin & Moon, 2006).…”
Section: Students With Ebdsupporting
confidence: 93%
“…These gifted students from Australia, Austria, and the United States also identified their preference for their teachers to demonstrate a range of pedagogical approaches (Vialle & Tischler, 2005). In her study of 63 teachers and 1,247 'highly able' students, Mills (2003) identified that, like their highly able students, those teachers considered to be highly effective teachers of gifted students "preferred abstract themes and concepts, were open and flexible, and valued logical analysis and objectivity" (p. 272). Mills (2003) identified that the most effective teachers of gifted students held advanced degrees in the content area in which they taught, yet had no formal training in gifted education.…”
Section: Determining Teacher Effectivenessmentioning
confidence: 99%
“…In her study of 63 teachers and 1,247 'highly able' students, Mills (2003) identified that, like their highly able students, those teachers considered to be highly effective teachers of gifted students "preferred abstract themes and concepts, were open and flexible, and valued logical analysis and objectivity" (p. 272). Mills (2003) identified that the most effective teachers of gifted students held advanced degrees in the content area in which they taught, yet had no formal training in gifted education. Additionally, Mills suggested that formal 'gifted training' for teachers may not be sufficient in selecting teachers for gifted students, and highlights the importance of selecting teachers who have both strong content knowledge and a passion for what they are teaching.…”
Section: Determining Teacher Effectivenessmentioning
confidence: 99%
“…Verschillende studies richten zich specifiek op de eisen die we mogen stellen aan docenten in programma's voor excellente en talentvolle studenten (bijv. Bangel, Moon, & Capobianco 2010;Mills, 2003). VanTasselBaska en Johnsen (2007) beschrijven specifieke competenties voor docenten in excellentieonderwijs.…”
Section: Docentprofessionalisering Voor Honoursonderwijsunclassified